1993
DOI: 10.1111/j.1440-1681.1993.tb01730.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic and Humoral Consequences of Chronic Infusion of Vasopressin in Conscious Rats

Abstract: 1. To determine the long-term haemodynamic and humoral effects of arginine vasopressin (AVP), a chronic intravenous infusion of AVP was performed in conscious Wistar normotensive rats. 2. AVP (1, 10, 50 or 100 ng/h) or saline as a vehicle control was infused continuously into the right jugular vein at a rate of 1 microL/h using an osmotic minipump for 7 days. 3. As a result, significant elevations of systolic blood pressure were observed in association with increases in plasma AVP concentration. Significant de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…This suggests that the functional effects are highly peptide selective, despite the fact that vasopressin has a high affinity for the rat brain oxytocin receptor (Audigier and Barberis, 1985). This functional selectivity is unlikely to arise from a degradation of vasopressin in the Alzet pump in vivo, because studies of the cardiovascular effects of vasopressin have shown that Alzet minipumps can sustain delivery of biologically active vasopressin over a 7 d period (Tsuchihashi et al, 1993). Second, although we cannot completely exclude a possible direct inhibition of the pituitary-adrenal axis attributable to oxytocin leakage from the ventricular system, this is unlikely because all evidence suggests that circulating oxytocin acts to stimulate rather than inhibit ACTH release at the pituitary (Antoni et al, 1983;Gibbs et al, 1984;Rivier and Shen, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the functional effects are highly peptide selective, despite the fact that vasopressin has a high affinity for the rat brain oxytocin receptor (Audigier and Barberis, 1985). This functional selectivity is unlikely to arise from a degradation of vasopressin in the Alzet pump in vivo, because studies of the cardiovascular effects of vasopressin have shown that Alzet minipumps can sustain delivery of biologically active vasopressin over a 7 d period (Tsuchihashi et al, 1993). Second, although we cannot completely exclude a possible direct inhibition of the pituitary-adrenal axis attributable to oxytocin leakage from the ventricular system, this is unlikely because all evidence suggests that circulating oxytocin acts to stimulate rather than inhibit ACTH release at the pituitary (Antoni et al, 1983;Gibbs et al, 1984;Rivier and Shen, 1994).…”
Section: Discussionmentioning
confidence: 99%